SALING SATINGI SEBAGAI MODEL RESOLUSI KONFLIK (STUDI KONFLIK PENGUASAAN LAHAN ANTARA PETANI DENGAN PETERNAK DI KABUPATEN SUMBAWA) - Lahmuddin Zuhri (Legal Spirit, 2017)
People in the archipelago view togetherness and harmony is a fundamental thing that sustains the existence of the community, both in the perspective of religiosity (ketauhidan), culture and economy. Society in the archipelago sees harmony is a grace as well as a mandate that must be maintained and kept. The role of local values in conflict resolutions can be modeled in many cases. An Anthropological approach is interesting to use, because Indonesians are culturally diverse, which can provide empirical explanations in social and community structures. The future of conflict resolutions can refer to the value of local community’s wisdom. With the principle of deliberation aims to involve or invite all parties to participate in community life, so that loyalty and adherence of the people to what is all agreed would be also maintained together, because the agreement is the fruit of thoughts and opinions in the nuances of kinship and “saling satingi” (mutual respect). “Saling satingi” is the noble value of society in Sumbawa can be used as a model, and the local wisdom in the archipelago can be utilized for resolving conficts in ethnic groups, religions, and races in maintaining unity, peace and community brotherhood. Key Words: Saling satingi, Conflict, Confidentiality